Urban Development of Cetinje and Bari Observed through of the Activities of Augusto Cesare Corradini (1900–1931) - Dajković, Aleksandar (Arhitektura i urbanizam, 2021)
The paper presents the chronological development of urbanism in Cetinje and Bari observed through the work of Italian architect Augusto Cesare Corradini (Augusto Cesare Corradini 1860–1932). Corradini contributed to the intensive urban and architectural development of Cetinje, the former capital of Montenegro, in the period 1900-1912, and Bari, the center of the Pula region, especially in the period 1905–1931. In these environments, he managed to define spaces with recognizable urban-architectural creations with an artistic sign, either as a segment of international eclecticism, such as the Russian legation in Cetinje (1900), Fizzarotti Palace (1906-1908) and Ingami Scalvini Palace (1923) or rationalism/modernism, such as the Fiat Palace (1925) and the pavilion of the Navigation Company of Puglia (1930) in Bari. Corradini especially defined the urban identity of cities with monumental buildings and complexes - the Government House in Cetinje (1910), and the Fiera del Levante (1928) in Bari. Aimed at acting in different environments and socio-political systems, his work had a special architectural expression with an undoubtedly semantic character. With new stylistic concepts and forms of spatial organization, he permanently influenced the modern urban-architectural processes of the mentioned cities, and the status of his work as national cultural goods confirms its importance as a unique combination of functional and decorative, artistic and technical. Through his integral view of urban trends and Corradini’s work in Cetinje and Bari, the strong influence of this Italian architect on the formation of unique urban matrices can be seen.
Keywords: Corradini; urban development; Cetinje; Bari